Building Youth Capacity for Healthier Communities: A 6-Year Evaluation of YPAR in Nutrition Education - Janessa Hartmann; Yu Meng; Irene Padasas; Alexa Erickson; Brandon Louie; Nancy Erbstein; Barbara MkNelly; Kamaljeet Khaira (Journal of Nutrition Education and Behavior, 2026)

Exploring Challenges, Successes, and Benefits of Implementing the Career Pathways Toolkit from SNAP-Ed Educator Perspectives - Irene Padasas; Yu Meng; Tamar Crump; Brandon Louie; Nancy Erbstein; Janessa Hartmann; Alexa Erickson (Journal of Nutrition Education and Behavior, 2026)

Between dispersion and recentring: Observations on post-pandemic migration flow and housing relocation behaviours in Montréal, Canada - Yu (Billie) Zhang; Nancy A. Ross; Ahmed El-Geneidy (Journal of Transport Geography, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Rational design on Cu-based electrochemical catalyst for efficient green ammonia production from nitrate: A review - Karuppiah Veerathangam; Nancy Anna Anasthasiya A; Yunliang Liu; Jingya Yin; Peter Phiri; Yaxi Li; Jingwen Yu; Yuanyuan Cheng; Naiyun Liu; Lei Xu; Haitao Li (Journal of Environmental Chemical Engineering, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Addressing Clinical Challenges in Aberrant Pharmacokinetics of Biologic Therapeutic Drugs: Investigating Sample Processing Procedure in the Immunoassays - Yih-Wen Chen; Olinda Davenport; Nancy Yu; Rachel Melendez; James Nugteren; Ihsan Nijem; Weili Yan; Robert Hendricks; Yuan Song (The AAPS Journal, 2025)
Bioanalytical Pharmacokinetics (PK) methods are designed for robust performance under rigorous regulatory compliance requirements to ensure the generated data is reliable and maintains integrity. In a phase 1 dose-finding clinical study, aberrant PK profiles of two co-administered biologics drugs were observed. Unexpectedly, we discovered high fill levels in collection tubes from the majority of samples. This led to the hypothesis that the highly filled tubes might cause difficulty in achieving complete sample thaw and thorough mixing at the time of sample analysis, potentially contributing to the abnormalities observed in the PK dataset. Evaluation of the impact of sample fill levels and processing procedure can be challenging since PK concentrations of study samples were unknown. Therefore, a systematic approach was employed to conduct a thorough examination using mock samples. The data illustrate a correlation between sample thawing and mixing process and the variability in the PK data. The concentrations from properly filled mock samples that underwent complete thawing and mixing showed 100% data reproducibility. In contrast, the concentrations from fully filled mock samples that did not follow the proper procedure showed sample recovery deviating by ± 30% from nominal value and exhibited considerable lack of precision . This data identified the root cause of aberrant PK, justifying revised sample preparation guidance and sample re-assay. Improved sample handling and subsequent reassay resolved the aberrant PK profile issues. In conclusion, this study reiterated that sample handling plays a crucial role in quality and reproducibility of PK data with immunoassays. Graphical Abstract

Evaluation of IrO2 catalysts doped with Ti and Nb at industrially relevant electrolyzer conditions: A comprehensive study - Xiang Lyu; Hung-Ming Chang; Haoran Yu; Nancy N. Kariuki; Jae Hyung Park; Deborah J. Myers; Jun Yang; Iryna V. Zenyuk; Alexey Serov (Chemical Engineering Journal, 2025)

Putting seedlings on the map: Trade‐offs in demographic rates between ontogenetic size classes in five tropical forests - Stephan Kambach; Helge Bruelheide; Liza S. Comita; Richard Condit; S. Joseph Wright; Salomón Aguilar; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; Nancy C. Garwood; Stephen P. Hubbell; Pei‐Jen Luo; Margaret R. Metz; et al. (Ecology, 2025)
All species must partition resources among the processes that underly growth, survival, and reproduction. The resulting demographic trade‐offs constrain the range of viable life‐history strategies and are hypothesized to promote local coexistence. Tropical forests pose ideal systems to study demographic trade‐offs as they have a high diversity of coexisting tree species whose life‐history strategies tend to align along two orthogonal axes of variation: a growth–survival trade‐off that separates species with fast growth from species with high survival and a stature–recruitment trade‐off that separates species that achieve large stature from species with high recruitment. As these trade‐offs have typically been explored for trees ≥1 cm dbh, it is unclear how species' growth and survival during earliest seedling stages are related to the trade‐offs for trees ≥1 cm dbh. Here, we used principal components and correlation analyses to (1) determine the main demographic trade‐offs among seed‐to‐seedling transition rates and growth and survival rates from the seedling to overstory size classes of 1188 tree species from large‐scale forest dynamics plots in Panama, Puerto Rico, Ecuador, Taiwan, and Malaysia and (2) quantify the predictive power of maximum dbh, wood density, seed mass, and specific leaf area for species' position along these demographic trade‐off gradients. In four out of five forests, the growth–survival trade‐off was the most important demographic trade‐off and encompassed growth and survival of both seedlings and trees ≥1 cm dbh. The second most important trade‐off separated species with relatively fast growth and high survival at the seedling stage from species with relatively fast growth and high survival ≥1 cm dbh. The relationship between seed‐to‐seedling transition rates and these two trade‐off aces differed between sites. All four traits were significant predictors for species' position along the two trade‐off gradients, albeit with varying importance. We concluded that, after accounting for the species' position along the growth–survival trade‐off, tree species tend to trade off growth and survival at the seedling with later life stages. This ontogenetic trade‐off offers a mechanistic explanation for the stature–recruitment trade‐off that constitutes an additional ontogenetic dimension of life‐history variation in species‐rich ecosystems.

Inhibition of glycolytic reprogramming suppresses innate immune-mediated inflammation in experimental amyotrophic lateral sclerosis - Lewis Yu; Nancy Wu; Okmi Choi; Khoa Dinh Nguyen (Inflammation Research, 2024)

Seasonal occurrence of toxic phytoplankton and phycotoxins at a mussel aquaculture site in Nova Scotia, Canada - Nancy I. Lewis; Rencheng Yu; Cheryl Rafuse; Michael A. Quilliam (Harmful Algae, 2023)

Quantitative characterization of filamentous fungal promoters on a single-cell resolution to discover cryptic natural products - Peng-Lin Wei; Jie Fan; Jingwen Yu; Zihui Ma; Xian Guo; Nancy P. Keller; Erwei Li; Chunbo Lou; Wen-Bing Yin (Science China Life Sciences, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

A hydrodynamic model for Galveston Bay and the shelf in the northern Gulf of Mexico - Jiabi Du; Kyeong Park; Jian Shen; Yinglong J. Zhang; Xin Yu; Fei Ye; Zhengui Wang; Nancy N. Rabalais (Ocean Science, 2019)
A 3-D unstructured-grid hydrodynamic model for the northern Gulf of Mexico was developed, with a hybrid s–z vertical grid and high-resolution horizontal grid for the main estuarine systems along the Texas–Louisiana coast. This model, based on the Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM), is driven by the observed river discharge, reanalysis atmospheric forcing, and open boundary conditions from global HYCOM output. The model reproduces the temporal and spatial variation of observed water level, salinity, temperature, and current velocity in Galveston Bay and on the shelf. The validated model was applied to examine the remote influence of neighboring large rivers, specifically the Mississippi–Atchafalaya River (MAR) system, on salinity, stratification, vertical mixing, and longshore transport along the Texas coast. Numerical experiments reveal that the MAR discharge could significantly decrease the salinity and change the stratification and vertical mixing on the inner Texas shelf. It would take about 25 and 50 d for the MAR discharge to reach the mouth of Galveston Bay and Port Aransas, respectively. The influence of the MAR discharge is sensitive to the wind field. Winter wind constrains the MAR freshwater to form a narrow lower-salinity band against the shore from the Mississippi Delta all the way to the southwestern Texas coast, while summer wind reduces the downcoast longshore transport significantly, weakening the influence of the MAR discharge on surface salinity along Texas coast. However, summer wind causes a much stronger stratification on the Texas shelf, leading to a weaker vertical mixing. The decrease in salinity of up to 10 psu at the mouth of Galveston Bay due to the MAR discharge results in a decrease in horizontal density gradient, a decrease in the salt flux, and a weakened estuarine circulation and estuarine–ocean exchange. We highlight the flexibility of the model and its capability to simulate not only estuarine dynamics and shelf-wide transport, but also the interactions between them.

Phosphorylated CRMP2 Regulates Spinal Nociceptive Neurotransmission - Jie Yu; Aubin Moutal; Angie Dorame; Shreya S. Bellampalli; Aude Chefdeville; Iori Kanazawa; Nancy Y. N. Pham; Ki Duk Park; Jill M. Weimer; Rajesh Khanna (Molecular Neurobiology, 2019)

Heroin Use Is Associated with Ruptured Saccular Aneurysms - Anil Can; Victor M. Castro; Yildirim H. Ozdemir; Sarajune Dagen; Dmitriy Dligach; Sean Finan; Sheng Yu; Vivian Gainer; Nancy A. Shadick; Guergana Savova; Shawn Murphy; Tianxi Cai; et al. (Translational Stroke Research, 2018)

Selection of a Ligand-Binding Neutralizing Antibody Assay for Benralizumab: Comparison with an Antibody-Dependent Cell-Mediated Cytotoxicity (ADCC) Cell-Based Assay - Yuling Wu; Ahmad Akhgar; Jia J Li; Binbing Yu; Cecil Chen; Nancy Lee; Wendy I. White; Lorin K. Roskos (The AAPS Journal, 2018)

Alcohol Consumption and Aneurysmal Subarachnoid Hemorrhage - Anil Can; Victor M. Castro; Yildirim H. Ozdemir; Sarajune Dagen; Dmitriy Dligach; Sean Finan; Sheng Yu; Vivian Gainer; Nancy A. Shadick; Guergana Savova; Shawn Murphy; Tianxi Cai; et al. (Translational Stroke Research, 2018)

Assessment of Correlation Between Early and Late Efficacy Endpoints to Identify Potential Surrogacy Relationships in Non-Hodgkin Lymphoma: a Literature-Based Meta-analysis of 108 Phase II and Phase III Studies - Rui Zhu; Dan Lu; Yu-Waye Chu; Akiko Chai; Michelle Green; Nancy Zhang; Jin Yan Jin (The AAPS Journal, 2017)

Assessing disparities in colorectal cancer mortality by socioeconomic status using new tools: health disparities calculator and socioeconomic quintiles - Nancy Breen; Denise Riedel Lewis; James Todd Gibson; Mandi Yu; Sam Harper (Cancer Causes & Control, 2017)

Receipt of mammography recommendations among White and non-White women before and after the 2009 United States Preventive Services Task Force recommendation change - Felisa A. Gonzales; Stephen H. Taplin; Mandi Yu; Nancy Breen; Kathy A. Cronin (Cancer Causes & Control, 2016)

Heroin Use Promotes HCV Infection and Dysregulates HCV-Related Circulating microRNAs - Yu Zhou; Li Sun; Xu Wang; Li Zhou; Jieliang Li; Manqing Liu; Fang Wang; Jinsong Peng; Xi’en Gui; Huaqing Zhao; Nancy Reichenbach; Dunjin Zhou; et al. (Journal of Neuroimmune Pharmacology, 2015)

The contribution of de novo and rare inherited copy number changes to congenital heart disease in an unselected sample of children with conotruncal defects or hypoplastic left heart disease - Dorothy Warburton; Michael Ronemus; Jennie Kline; Vaidehi Jobanputra; Ismee Williams; Kwame Anyane-Yeboa; Wendy Chung; Lan Yu; Nancy Wong; Danielle Awad; Chih-yu Yu; Anthony Leotta; et al. (Human Genetics, 2014)

Splenic Immune Cells in Experimental Neonatal Hypoxia–Ischemia - Nancy Fathali; Robert P. Ostrowski; Yu Hasegawa; Tim Lekic; Jiping Tang; John H. Zhang (Translational Stroke Research, 2013)

Genome of papaya, a fast growing tropical fruit tree - Ray Ming; Qingyi Yu; Paul H. Moore; Robert E. Paull; Nancy J. Chen; Ming-Li Wang; Yun J. Zhu; Mary A. Schuler; Jiming Jiang; Andrew H. Paterson (Tree Genetics & Genomes, 2012)

Vibrational and thermodynamic properties of Ni3S2 polymorphs from first-principles calculations - Yonggang G. Yu; Nancy L. Ross (Physics and Chemistry of Minerals, 2011)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Fruit Development, Ripening and Quality Related Genes in the Papaya Genome - Robert E. Paull; Beth Irikura; Pingfang Wu; Helen Turano; Nancy Jung Chen; Andrea Blas; John K. Fellman; Andrea R. Gschwend; Ching Man Wai; Qingyi Yu; Gernot Presting; Maqsudul Alam; et al. (Tropical Plant Biology, 2008)

Transactivation by expression of the hepatitis B virus X protein with an inducible system - Azliyati Azizan; Yu-Sheng Cong; Ken Shain; Shih-Chang Tsai; Ya-Li Yao; Nancy Olashaw; Edward Seto (Molecular Biology Reports, 1998)

Srbl maps to mouse Chromosome 5 in a region harboring putative QTLs for plasma lipoprotein levels - Carrie L. Welch; Yu-Rong Xia; Ling-Jie Gu; Dietrich Machleder; Margarete Mehrabian; Ping-Zi Wen; Nancy Webb; Willem J. S. de Villiers; Deneys van der Westhuyzen; Aidons J. Lusis (Mammalian Genome, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)